МОДЕЛИ СОЗДАНИЯ АГРОХОЛДИНГА СРАВНИТЕЛЬНО-ПРАВОВОЙ АСПЕКТ - Дударенко, Виктор Валерьевич (SUPREMANCE OF LAW, 2018)
In the article “Models of creating an agricultural holding: a comparative legal aspect” describes ways of creating an agricultural holding with the help of various legal mechanisms. The author analyzed the peculiarities of the models of creation of agricultural holding and made their comparative analysis.